Late Occurrence of Transient Advanced Second Degree Atrioventricular Block after Successful Transcatheter Cryoablation of Atrioventricular Nodal Reentry Tachycardia - Maria Malaya C. Dorotan-Guevara; Michael S. Crapanzano; Christopher S. Snyder (Case Reports in Cardiology)
Late occurrence of atrioventricular nodal block is an extremely rare occurrence after radiofrequency catheter modification of the slow pathway and has yet to be reported after cryoablation. We report a case of late transient advanced second degree atrioventriuclar block after cryomodification of the slow pathway.